Faktor-Faktor yang Berpengaruh Terhadap Nilai Perusahaan Selama Pandemi Covid-19 - Prasetyo, Ajeng Ayu Indy; T, Sutrisno (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study examines the factors affecting firm value during the COVID-19 pandemic, including profitability, leverage, financial distress, and Dividend Payout Ratio (DPR). This study applies ex post facto design with a quantitative approach involving the secondary data from the companies’ financial statements analyzed by multiple linear regression. The samples include 90 companies listed on the Indonesia Stock Exchange (IDX) selected through a disproportionate stratified random sampling method. The results indicated that leverage with the proxy of Debt to debt-equity ratio (DER) and financial distress had a positive effect on firm value, while profitability with the proxy of Return on Equity (ROE) and Dividend Payout Ratio (DPR) had no effect on firm value. Simultaneously, profitability, leverage, financial distress, and Dividend Payout Ratio (DPR) had an effect on firm value